Penafsiran Riba Studi Komparatif Antara Kaum Modernis dan Neo-Revivalis - A. Taufiq Buhari (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2018)
Interpretation of interest as applied to modern banking today, there are still differing views. Modernists view the prohibition of usury as being understood by emphasizing the rational aspect. Through this understanding, the element of injustice becomes a central issue for its prohibition. They seem to tolerate if their savings are based on the mudharabah system, because they can be found on the basis of their legitimacy. In addition, it is permissible if really forced (dharuri) or really needs (hajat). Also allows productive loan interest while consumptive loan interest is not allowed. While the Neo Revivalists were of the view that the prohibition of usury was understood legally formally as conceptualized in Islamic law. This view emphasizes the legal form of usury as expressed in Islamic law. They assert that the statement set out in the Qur'an must take its literal meaning, regardless of what was practiced in the pre-Islamic period. Whatever the circumstances, the lender does not have the right to receive additions to and exceed the principal